Desenvolvimento econômico e indústria : a indústria 4.0 e o aprimoramento tecnológico da produção local - Sampaio, Marco Túlio Brasiel (2022)
During the 30's and 80's of the last century, there were great initiatives of the Brazilian national state that aimed to accelerate the development of the national economy. In this respect, the influence of the developmental theories of Celso Furtado and other economists from ECLAC (Economic Commission for Latin America and the Caribbean) ended up laying the foundations for the desired development in the consolidation of Brazil's industry. Production complexity, production chains and the international division of labor are constantly changing. Thinking in this way, the industry, which has all these characteristics, continues to evolve and be improved. In this work, the new Industry 4.0, or advanced manufacturing, was approached, its characteristics and influences on economic activities, drawing a parallel between the necessary conditions for its implementation and the conditions that are presented locally. A review was made of Schumpeterian theories that refer to technological development as the main engine of economic development, dealing with regional development, industry 4.0 and economic theory. To obtain the research results, two studies were carried out, the first, a bibliometric review of the works published between 2017 and 2022 within the works contained in the Scientific Electronic Library Online (SciELO) and Capes Periodicals databases. This first study served as a guide for the second study, because through it the overview of how industry 4.0 evolves in Brazil was obtained. The second study carried out was a data collection that aimed, through the application of a survey, to visualize the extent to which local production, in the State of Sergipe, is placed within what is expected for an industry with characteristics of the fourth industrial revolution. , as well as investigated the extent to which the necessary foundations exist for such technologies to be locally deployed.